2020
DOI: 10.3846/btp.2020.10463
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee Characteristics and Sustainability Performance in Nigerian Listed Banks

Abstract: This study investigates the influence of audit committee characteristics on the sustainability disclosure among the Nigerian listed banks. Using the Fixed Effect regression estimator of panel data for ten (10) listed banks in Nigeria over the period of 2014–2016, the result shows that the influence of audit committee independence and gender diversity of audit committee are significantly positive on the sustainability disclosure. However, the audit committee magnitude has a negative and significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…On the other hand, other studies did not support such a positive association or found a negative relationship (Madi et al, 2014;Bicer and Feneir, 2019;Adegboye et al, 2020).…”
Section: Audit Committee Size and Csrdmentioning
confidence: 91%
See 3 more Smart Citations
“…On the other hand, other studies did not support such a positive association or found a negative relationship (Madi et al, 2014;Bicer and Feneir, 2019;Adegboye et al, 2020).…”
Section: Audit Committee Size and Csrdmentioning
confidence: 91%
“…Most of the previous research found significant positive association between AC independence and CSRD (i.e., Madi et al, 2014;Appuhami and Tashakor, 2017;Buallay and Al-Ajmi, 2019;Adegboye et al, 2020). However, other studies did not find a relationship between AC independence and CSRD (i.e., Li et al, 2012;Othman et al, 2014;Musallam, 2018).…”
Section: Audit Committee Independence and Csrdmentioning
confidence: 94%
See 2 more Smart Citations
“…The Green Innovation Concept or Green Innovation as an effort to reform the process or human activity is running along with an environmentally friendly lifestyle (Green Lifestyle) and a green economy and support one another (Owen et al, 2018). At first glance it may sound ordinary, but in fact green innovation can provide extraordinary benefits not only for humans but also the earth's soil that supports sustainable life (Adegboye et al, 2020) Innovation of creating value is often identified with "big reforms" that can only be carried out by large institutions or companies, but in fact innovation belongs to anyone, including farmers in rural areas far from urban areas. Innovation can come from anyone, no matter the level of education.…”
Section: Digital and Green Innovative Strategymentioning
confidence: 99%